APLIKASI SISTEM INFORMASI GEOGRAFI UNTUK PENGHITUNGAN KOEFISIEN ALIRAN DAERAH ALIRAN SUNGAI (DAS) CILIWUNG - Indriatmoko, Robertus Haryoto; Wibowo, V. Ery (Center for Environmental Technology, 2007)
According to Cook, drainage basin characteristics factor yielding high surface stream are 1. Relief 2. Infiltration 3. Landuse, and 4. Drainage density. These physical parameter is use to determine runoff coefficient of catchment area, with application of Geographical Information System (GIS) application on Ciliwung catcment area above Depok. Steps to analyse of runoff coefficient are scoring of each classification of relief, infiltration, landuse and drainage density, and then all of the four maps which have score are overlay to become a map of unit land. Runoff coefficient hereinafter is calculated and found out that runoff coefficient of Ciliwung catchment area is 0, 58.Ã‚Â Ã‚Â Katakunci : GIS, SIG, metode Cook, metode Bridge Branch, runoff coeffisient, catchment area, DAS, Ciliwung, relief, infiltration, landuse, drainage density, informasi, peta tematik.